2004
DOI: 10.1039/b313804f
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the dual luminescence of twisting molecules. The case of substituted 2,3-naphthalimides

Abstract: The effect of high pressure (up to 5 kbar) has been studied for triacetin solutions of 2-phenyl-2,3-dihydro-1H-benzo[f]isoindole-1,3dione 1 (N-phenyl-2,3-naphthalimide) and its 3-fluorophenyl- (2), 4-carbethoxyphenyl(4) and 4-methoxyphenyl (5) derivatives which all show dual fluorescence. When the N-phenyl group is unsubstituted (compound 1) or substituted with electron-attracting groups (2 and 4), the increase of pressure over the solution decreases slightly the emission at the long-wavelengths (LW) and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…It can be concluded that the partial conjugation between the aryl and imide moiety decreases the negative charge on the oxygen atoms resulting in a decrease in the hydrogen-bond forming ability. The aryl -imide dihedral angles are around 43.5 o and 59.2 o for the PMPN [10] and the N-phenyl derivative [11], respectively; while for DMPN nearly 90 O angle is expected [5]. …”
Section: Uv Spectra and Ground State Complex Formationmentioning
confidence: 94%
“…It can be concluded that the partial conjugation between the aryl and imide moiety decreases the negative charge on the oxygen atoms resulting in a decrease in the hydrogen-bond forming ability. The aryl -imide dihedral angles are around 43.5 o and 59.2 o for the PMPN [10] and the N-phenyl derivative [11], respectively; while for DMPN nearly 90 O angle is expected [5]. …”
Section: Uv Spectra and Ground State Complex Formationmentioning
confidence: 94%
“…Photoexcitation (λ exc = 355 and 400 nm) of triad TAN results in the generation of local excited states of either A or N; (T–A–N) → (T– 1 A–N)* or (T–A– 1 N)*; the state (T– 1 A–N)* through rapid energy transfer populates (T–A– 1 N)*. Naphthalimides are known to undergo efficient ISC with short singlet state lifetimes (τ f ) and low fluorescence quantum yields; hence the (T–A– 3 N)* state gets populated via ISC from the (T–A– 1 N)* state (Figure ). The short centroid-to-centroid distance between A and N units (5.40 Å, Figure S18, SI) in TAN allows sufficient exchange interaction and spin correlations to give 1 (T •+ AN •– ) and 3 (T •+ AN •– ) wherein the latter state is primarily populated via a T–A– 3 N state. , Geminate charge recombination of 1 (T •+ AN •– ) could also result in the population of (T–A– 3 N)*.…”
Section: Resultsmentioning
confidence: 99%
“…11 The charge-transfer (CT) characteristics of NI excited states have also been studied in organic materials, such as donor−acceptor systems for solar cells, 12 organic light-emitting diodes (OLEDs), 13 sensors for metal ions and protons, 14−18 and potential optical switches operating in the picosecond time scale. 19 Interestingly, when the imide nitrogen is substituted by arenes, NIs can be designed to display dual-fluorescence and in certain cases panchromatic emission. 6,20,21 To date, NIs hold the unique advantage of emitting white light with the smallest molecular architecture among so-called single-emitter dyes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…(2) the nature of substituents located on the naphthalene ring, 1,[4][5][6]19,22,29,31 such as electron-withdrawing groups or electron-donating groups, and (3) the nature of substituents attached to the imide group. Regardless of the constitutional isomerism for N-aryl-1,2-NI, -2,3-NI, and -1,8-NI (Figure 1), a common similarity exists: electron-withdrawing groups (EWG) on either the naphthalene ring or phenyl ring promotes SW emission, and electron-donating groups (EDG) on both sides promote LW emission.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation